The Schultz Polynomial of Zigzag Polyhex Nanotubes - Eliasi, Mehdi; Taeri, Bijan (Asian Journal of Chemistry, 2010)
The Schultz polynomial, S(G,x), of a molecular graph G has the property that its first derivative at x=1 is equal to the Schultz index of graph. Ivan Gutman discovered that in the case of G is a tree, S(G,x), has closely related to the Wiener polynomial of G. In this paper, we find the exact expression for Schultz polynomial of TUHC6 [2p; q], the zigzag polyhex nanotubes, and obtain a relation between Schultz and Wiener polynomials of TUHC6 [2p; q].